Can a hierarchical ordering of alternative technological concepts for decarbonizing industrial energy systems minimize mitigation costs? - Oluleye, Gbemi; Bishay, Doss; Kas, Baptiste (Frontiers in Sustainability, 2023)
Abstract Integration of alternative technological concepts such as switching to alternative fuels, advanced energy efficiency, and carbon capture & storage (CCS) in existing industrial energy systems can prove highly effective at minimising emissions; however, their adoption is low since solutions using these concepts raise costs considerably. The hypothesis of this work is a hierarchical combination of these concepts can reduce mitigation cost. To this end a mixed method approach is applied combining energy simulation with a novel Mixed Integer Linear Programming model developed to explore 48 alternative solutions to make IES more sustainable. The method was applied to the most common IES configurations. Results show that the added cost of integrating alternative technological concepts are lowered when energy efficiency via direct heat recovery is explored first in an optimisation-based hierarchy of options. The hierarchy is advanced energy efficiency before fuel and technology switching or integrating CCS. This means process integration can pay for steeper reductions in carbon emissions. Integrating alternative technological concepts optimally and hierarchically reduced emissions by 61%, and costs by 55.7% compared to a partial integration for a heat-only business-as-usual IES. Even though switching to an alternative fuel (blue hydrogen) reduces carbon emissions by 72%, costs increase by at least 3% compared to a system using fuel gas and fuel gas. A hierarchical integration of blue hydrogen reduces cost by 47% and carbon emissions by 88.7%. Partial integration of CCS reduces carbon emissions by 36% but costs increase by 89%, with full integration using optimisation and the hierarchy costs only increase by 6.3%. therefore, the cost-effectiveness of integrating alternative technological concepts is highly influenced by the hierarchy which seeks to minimise demand for energy from industrial processes first, then increase the supply efficiency of IES, and before switching to alternative fuels and technologies.